Long-term ceramic matrix composite for aeroengine - Chaokun Song; Fang Ye; Laifei Cheng; Yongsheng Liu; Qing Zhang (Journal of Advanced Ceramics, 2022)
Abstract Three strategies were proposed to prolong the service life of continuous fiber-reinforced silicon carbide ceramic matrix composite (CMC-SiC), which served as thermal-structure components of aeroengine at thermo-mechanical-oxygenic coupling environment. As for some thermal-structure components with low working stress, improving the degree of densification was crucial to prolong the service life, and the related process approaches were recited. If the thermal-structure components worked under moderate stress, the matrix cracking stress (σ mc) should be improved as far as possible. The fiber preform architecture, interface shear strength, residual thermal stress, and matrix strengthening were associated with σ mc in this review. Introducing self-healing components was quite significant with the appearance of matrix microcracks when CMC-SiC worked at more severe environment for hundreds of hours. The damage can be sealed by glass phase originating from the reaction between self-healing components and oxygen. The effective self-healing temperature range of different self-healing components was first summarized and distinguished. The structure, composition, and preparation process of CMC-SiC should be systematically designed and optimized to achieve long duration target.